TEC kinase stabilizes PLK4 to promote liver cancer metastasis. (1st January 2022) - Yeung, Sai-Fung; Zhou, Yuan; Zou, Wenjun; Chan, Wing-Lim; Ching, Yick Pang
Abstract: Aberrated PLK4 expression has been reported in different malignancies and causes centrosome amplification, aneuploidy, and genomic instability. However, the mechanism by which PLK4 is regulated in carcinogenesis remains not fully characterised. Here, we showed that PLK4 was overexpressed in human HCC and overexpression of PLK4 predicted poorer patient prognosis. Unexpectedly, we found that induced expression of PLK4 promotes, but knockdown of PLK4 inhibits, HCC cell migration and invasion. Mechanistically, we found that TEC tyrosine kinase, which also promotes HCC cell migration, stabilizes PLK4 by phosphorylation. TEC directly phosphorylates PLK4 at tyrosine 86 residue, which not only stabilizes the protein but also enhances PLK4-mediated HCC cell invasion. Further investigation by transcriptome sequencing indicated that PLK4 promotes the phosphorylation of focal adhesion kinase to regulate the focal adhesion pathway in HCC cell migration. Taken together, our results demonstrated that PLK4 plays an important role in HCC metastasis and revealed for the first time the mechanism by which PLK4 promotes HCC metastasis via TEC phosphorylation. Highlights: PLK4 is upregulated in HCC and promote invasiveness of HCC cells. TEC stabilize PLK4 by phosphorylating tyrosine 86 residues. PLK4 promotes HCC cell invasion by regulating the focal adhesion pathway.